2019
DOI: 10.12659/msm.916662
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Targets and the Biological Mechanisms of Formononetin for Alzheimer’s Disease: A Network Analysis

Abstract: Background This study aimed to identify the pharmacological targets and mechanisms of action of the traditional Chinese medicine, formononetin, in the treatment of Alzheimer’s disease (AD) using network pharmacological analysis. Material/Methods Targets of AD were obtained by using DisGeNET gene discovery platform, the herbal ingredients target (HIT) database, the SuperPred, and the SwissTargetPrediction compound target prediction platforms. Pathogenic and therapeutic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…A network pharmacology-based approach has previously proved successful in revealing treatable targets and mechanisms from bioinformatics assays [ 14 ]. Indeed, in our previous studies, we have identified the pharmacological biotargets of several bioactive agents used to manage clinical diseases [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A network pharmacology-based approach has previously proved successful in revealing treatable targets and mechanisms from bioinformatics assays [ 14 ]. Indeed, in our previous studies, we have identified the pharmacological biotargets of several bioactive agents used to manage clinical diseases [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…And then, the identifiable findings were introduced to the Cytoscape software, in which the setting of network analyzer was used to optimize the PPI data of VC against CG following topological criteria. The core biotargets of VC against CG were screened and identified according to the degree values of topological data …”
Section: Methodsmentioning
confidence: 99%
“…The core biotargets of VC against CG were screened and identified according to the degree values of topological data. 12,13…”
Section: Ppi Network Assay and Identification Of Core Targetsmentioning
confidence: 99%
“…In brief, all therapeutic targets of calycosin against NPC were uploaded into a web-based Database of Functional Annotation Bioinformatics Microarray Analysis (DAVID) to produce optimal functional processes and signalling pathways of calycosin against NPC. Based on the settings of the -Log pvalue, a three-dimensional bar chart of biological processes and signalling pathways of calycosin against NPC was created [14] .…”
Section: Identification Of Molecular Functions and Pathways Of Calycomentioning
confidence: 99%